The one-pot synthesis of CuNi nanoparticles with a Ni-rich surface for the electrocatalytic methanol oxidation reaction. Issue 5 (16th January 2020) - An, Yajing; Ijaz, Hamza; Huang, Ming; Qu, Jianqiang; Hu, Shi
Abstract : Polyhedral Cu–Ni alloy nanoparticles with a Ni-rich surface were synthesized, and they exhibit very high activity during the methanol oxidation reaction. Abstract : The use of fuel cells is one of the most promising renewable energy strategies, but they still suffer from many limitations. The high mass enthalpy of hydrogen as a fuel comes at the cost of inconveniences and risks associated with storage, transportation and utilization, while the high performance of Pt catalysts in commercial fuel cells is limited by their high cost, low earth abundance, and poor stability as a result of CO intermediate poisoning. To circumvent these dilemmas, direct methanol fuel cells (DMFCs) were developed, using methanol as a fuel and Ni as the anode catalyst. Thanks to the condensed form of the fuel, DMFCs are considered as the most promising fuel-cell solution for portable electronic devices. Usually, other elements have to be introduced into Ni-based catalysts to modify the active sites to provide better alternatives to pristine Ni metal in terms of activity and stability. In this study, we provide a mild synthetic method for the preparation of CuNi alloy nanoparticles. The proper alloying ratio leads to the suitable modification of the electronic structure of Ni, which promotes the MOR catalytic reaction on the NiCu alloy. The NiCu alloy catalyst exhibits a mass current density of 1028 mA mgmetal −1 for the MOR at 1.55 V ( vs. RHE), which is among the best values obtained from similarly prepared Ni-based catalysts.